Corporate governance and firm value: empirical evidence from electric utilities (2019)
This study analyzes the impact that Corporate Governance has in the firm value of electric utilities in 2018. It develops the description of the role that Corporate Governance plays in an enterprise, making an emphasis in the behaviors that are seen towards the firm innovation capacity and the importance of choosing the electric industry as the sample of analysis. Data availability was a major constraint to assess the proposed relationship. Nevertheless, an OLS regression was performed for a 2018 cross-sectional database evaluating firm value, measured by the Tobin’s Q ratio, against the governance rating of the CSRHub and several other control variables. Our results show a positive and significant relationship between the quality of corporate governance and the value of the company. In view of the restrictions caused by the data availability for an analysis of this kind, suggestions are made for further research that can be held to strengthen the results shown in this study.